2020
DOI: 10.1159/000507123
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Feasibility Study of Single-Shot Antibiotic Prophylaxis in Transrectal Focal Ablation of Prostate Cancer

Abstract: Introduction: Urinary tract infections (UTI) represent the most frequent complications after transrectal focal ablation of prostate cancer. Single-shot antibiotic prophylaxis for prevention has not yet been described. Methods: In this cohort study of patients who received a high-intensity focused ultrasound (HIFU) ablation of prostate cancer within a registered prospective single-arm trial, we analyzed posttreatment UTI (≤30 days after HIFU) related to perioperative antibiotic management in an exploratory anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In our experience sepsis after focal treatment is very rare. A recent prospective study has reported a single shot antibiotic prophylaxis prior to HIFU treatment with similar infectious rates as in the literature (29). A consensus on antibiotic prophylaxis choice and duration for focal treatments is yet to be achieved.…”
Section: Peri-operative Complicationsmentioning
confidence: 89%
“…In our experience sepsis after focal treatment is very rare. A recent prospective study has reported a single shot antibiotic prophylaxis prior to HIFU treatment with similar infectious rates as in the literature (29). A consensus on antibiotic prophylaxis choice and duration for focal treatments is yet to be achieved.…”
Section: Peri-operative Complicationsmentioning
confidence: 89%